Canine neutrophils activate effector mechanisms in response to Leishmania infantum - Pereira, Maria; Valério-Bolas, Ana; Santos-Mateus, David; Alexandre-Pires, Graça; Santos, Marcos; Rodrigues, Armanda; Rocha, Hugo; Santos, Ana; Martins, Catarina; Tomas, Ana; Passero, Filipe [UNESP]; da Fonseca, Isabel Pereira; et al. (Elsevier, 2017)
Canine leishmaniosis caused by L. infantum is a severe zoonotic disease. Although macrophages are the definitive host cells, neutrophils are the first cells to encounter the parasite soon after its inoculation in the dermis by the phlebotomine vector. To study the interaction of dog neutrophils and L. infantum promastigotes, blood neutrophils were isolated from healthy donors and the infection was established in vitro. In the majority of the dogs, L. infantum was efficiently phagocytized by neutrophils, and oxidative (superoxide production) and non-oxidative (neutrophil elastase exocytosis) intracellular effector mechanisms were activated, but the release of neutrophil extracellular traps was minimized. Furthermore, promastigotes and culture supernatants induced neutrophil migration, but the prior contact with Leishmania inhibits chemotaxis, which might contribute to neutrophil retention at the inoculation site. Neutrophil-parasite interaction resulted in a decrease in parasite viability, although some intracellular promastigotes survive and maintain their proliferative capacity. These findings indicate that dog neutrophils are competent effector cells able to control the initial L. infantum infection. However, some parasites evade intracellular effector mechanisms and can be transferred to the definitive host cell, the macrophage, contributing to the development of canine leishmaniosis.
Keywords: Canine leishmaniosis; Electron microscopy; Neutrophil elastase; Neutrophil extracellular traps; Neutrophils; Superoxide